Decarbonizing the oil refining industry: A systematic review of sociotechnical systems, technological innovations, and policy options. (July 2022) - Griffiths, Steve; Sovacool, Benjamin K.; Kim, Jinsoo; Bazilian, Morgan; Uratani, Joao M.
Abstract: The oil refining industry, which was established in the mid-19th century, has become a foundation of modern society. While the refining of crude oil to produce transportation fuels, petrochemical feedstocks and a variety of other products has brought manifold benefits, it has also led to the global proliferation of greenhouse gas emissions as well as local air pollution from the combustion of fossil fuels. The industry is therefore confronted with a growing need to decarbonize its operations, as well as to support decarbonization of the end use sectors that it directly enables. This paper provides a systematic and critical literature review to uncover the means by which the oil refining industry can decarbonize and evolve as part of an increasingly carbon constrained future. A sociotechnical perspective is used to understand the full range of industrial and economic activities where a decarbonized oil refining industry is expected to remain important and to provide the framework to assess key technical, economic, social and political factors that will likely impact the evolution of the oil refining industry. We highlight key opportunities for this industry to decarbonize while also exposing gaps in the existing literature concerning its decarbonization. The insights provided are expected to support policy makers, researchers and practitioners with the tools needed advance a low-carbon transition of the oil refining industry.